Optimasi Penerapan Metode Stepping Stone untuk Optimasi Pengiriman Barang pada RJ. Logistic Cargo Nabire - Taran, Leni Paula; Suhendra, Chistian Dwi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Goods Delivery is preparing the delivery of goods from the building to the destination that has been adjusted to the ordering and delivery documents and in conditions that comply with the goods handling requirements. Just like RJ. Logistics Cargo, is a cargo expedition and entrustment service located at Jln. Surabaya Karang Mulia, Nabire, Central Papua. RJ. Logistics Cargo also strives to optimize the delivery of goods to consumers. RJ. Logistics Cargo provides solutions to consumers who need reliable and fast delivery of goods. So far, RJ has been considering it. Logistics Cargo in arranging routes is only limited to capacity, weight of goods transported and location, never considering whether the distance traveled on the route is minimal or not. Delivery routes are determined randomly according to the driver's intuition. Therefore, an important thing that freight forwarding companies must pay attention to apart from transportation is cost optimization. Cost optimization needs to be applied to various company activities, and one of the things companies do is to optimize transportation costs. So it can help solve the problem of distributing products from sources to several destinations and reduce total distribution costs. By optimizing transportation costs, it is useful to help distribute effectively and efficiently with minimum costs.